2021
DOI: 10.1111/1748-5967.12504
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of breast meat traits of broilers fed different amounts of Hermetia illucens and Protaetia brevitarsis seulensis powder

Abstract: The aim of this study was to investigate the effects of different levels of Hermetia illucens (HI) and Protaetia brevitarsis seulensis (PBS) powder on breast meat of broilers during storage. A total of 400 1-d-old Arbor Acres broilers were randomly divided into four treatments; each treatment group included four replicate pens with 25 birds per pen. Broilers were fed basal diets supplemented with 0.5%, and 1% HI powder or 1.5% PBS powder or only basal diets without HI or PBS. Traits such as meat quality, color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…2021, Choi SU et al . 2021; Choi & Chung 2021). Moreover, insects (house fly maggots) can also be used to address challenges such as environmental pollution caused by odor, livestock waste, and food waste (Boushy 1991; Van Huis 2022).…”
Section: Introductionmentioning
confidence: 99%
“…2021, Choi SU et al . 2021; Choi & Chung 2021). Moreover, insects (house fly maggots) can also be used to address challenges such as environmental pollution caused by odor, livestock waste, and food waste (Boushy 1991; Van Huis 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Choi et al [ 115 ] carried out the determination of the antioxidant capacity on breast meat of broilers for the purpose of investigate the influence of the use of different levels of Hermetia illucens and Protaetia brevitarsis seulensis powders in the feeding of these animals as cheaper animal protein sources. Specifically, Choi et al [ 115 ] employed the DPPH • test through which they observed that supplementation with both insect powders significantly improved antioxidant capacity of breast meat at day 0 compared to a basal diet. However, they also observed that after 7 days of refrigerated storage, the inclusion of powders in the diet did not maintain this improvement in antioxidant capacity of meat.…”
Section: Applications Of Antioxidant Assays In Meat and Meat Productsmentioning
confidence: 99%
“…These findings showed the greater effectiveness of wheat germ oil (natural α-tocopherol) compared to synthetic α-tocopherol. Additionally, Choi et al [115] carried out the determination of the antioxidant capacity on breast meat of broilers for the purpose of investigate the influence of the use of different levels of Hermetia illucens and Protaetia brevitarsis seulensis powders in the feeding of these animals as cheaper animal protein sources. Specifically, Choi et al [115] employed the DPPH • test through which they observed that supplementation with both insect powders significantly improved antioxidant capacity of breast meat at day 0 compared to a basal diet.…”
Section: Study Of the Influence Of Animal Diet On The Antioxidant Capacity Of Meatmentioning
confidence: 99%
“…Based on numerous studies (Table 1), the black soldier fly as meal or fat in poultry diets has no [39][40][41][42][43][44][45][46][47][48] or limited influence [41,42,[47][48][49][50] on physical meat quality (pH, colour, water holding capacity (WHC), shear force) of broiler's chicken, quail, barbary partridge, and muscovy duck. Similarly, the poultry meat proximate composition also showed alternate results, and they do not seem related to the insect meal inclusion level.…”
Section: Poultrymentioning
confidence: 99%
“…However, most of the studies did not observe changes in the oxidation of meat lipids in animals fed black soldier fly [40,51,53]. However it is interesting to note that Choi et al [39] observed a significantly low TBARS value on fresh meat after 7 days of refrigerated storage, and authors attributed it to the improved antioxidant activity (measured through the DPPH radical scavenging activity) of the meat due to the inclusion of the black soldier fly in the diet.…”
Section: Poultrymentioning
confidence: 99%